Pengaruh Modal Intelektual dan Kebijakan Dividen Terhadap Nilai Perusahaan - Fakhrudin, Muchamad Imam; Mildawati, Titik (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThe purpose of this research is to examine the influence of intellectual capital and dividend policy to the firm value.Intellectual capital is measured by using value added intellectual coefficient (VAIC), devidend policy is measured byusing dividend payout ratio (DPR) formula and firm value is measured by using price to book value (PBV) formula.This research has been done by using quantitative approach by using multiple linear regressions analysis. The data isthe secondary data which is originated from property, real estate, and building construction companies which are listedin Indonesia Stock Exchange in 2011-2015 periods. The sample collection has been carried out by using purposivesampling method. The data processing has been done by using SPSS 23rd version. The resul of the research shows thatintellectual capital give positive influence to the firm value which means that when the value of intellectual capital isgetting large, the firm value is getting large as well. Dividend policy gives positive influence to the firm value whichmeans that when the dividend which is paid to the stockholders is getting large, the firm value is getting large as well.Keywords: Intellectual Capital (VAIC), Dividend Policy (DPR), Firm value (PBV).